SEJARAH DAN MISTERI GELOMBANG MERGER : Sebuah Perspektif Amerika dan Inggris - Suharyono Suharyono (Jurnal Ilmu dan Budaya, 2020)
With the main reference of the article "The History and Mystery of the Merger Wave: A UK and US Perspective" and relating it to the situation in Indonesia, the following policy implications are worth mentioning, among others: That mergers and acquisitions are essentially unexpected cases, because the company was established with a clear vision, mission and goals. However, due to various changes in the internal and external environment, the events of mergers and acquisitions are inevitable. However, because mergers and acquisitions have aspects that have a wide impact on all stakeholders, mergers and acquisitions should not be used as the primary choice in overcoming the difficulties of the policy implications of the merger and acquisition, so mergers and acquisitions can only be made if: (1) the company is in a state healthy and intends to improve his health through mergers and acquisitions, as an effort to encourage internal growth, (2) not the company due to environmental changes. With the extent of conflicting with the interests of all company stakeholders, namely the board of directors, employees, government and society, (3) consider and comply with legal aspects of legality, and have social responsibility so that its implementation does not cause unfair business competition and kill its competitors in the form of monopile, (4) placing mergers and acquisitions as strategic policies so that they must be done transparently, with the right procedures and stages and through careful preparation by adhering to the principle of prudence in business (prudencial principle).